Passiflora incarnata in the treatment of anxiety: An integrative review (Research, Society and Development, 2023)
Anxiety is a common and normal emotion, being a warning sign and part of the life of any human being. However, when intense and lasting, negatively influencing the individual's daily life and quality of life, it is characterized as pathological anxiety. Allopathic drugs prescribed to treat anxiety have been shown to cause more adverse reactions compared to therapeutic products of plant origin. Passiflora incarnata can be an effective, safe alternative with fewer adverse reactions compared to conventional medications. The studies presented in this article demonstrated the efficacy and safety of P. incarnata in the face of anxiety, it was also noticed that its use can be an interesting alternative to minimize anxiety, however, some authors suggested the need for further studies. This article is an integrative literature review and aims to present clinical studies that used Passiflora incarnata as a means of controlling anxiety. The Scientific Eletrônico Library (Scielo), PubMed and Google Scholar databases were used, as well as articles published from 2000 to 2023. In addition, 25 references were used to produce the article, in which 7 articles were related to studies clinicians, for presenting studies related to the use of P. incarnata to control anxiety.